Preparation and use method of tannic acid complex iron for enhancing dehydration performance of ozonized sludge
By preparing tannin complex iron and using it in the ozone oxidation system, the problem of poor sludge dehydration performance is solved, efficient sludge dehydration is achieved, the moisture content of the mud cake is reduced, and the sludge treatment and disposal efficiency is improved.
Patent Information
- Application Number
- CN202510076997.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-04-29
AI Technical Summary
The dehydration performance of the sludge is poor, resulting in the high moisture content of the mud cake obtained by filtration after conventional aluminum salt or iron salt coagulant treatment and treatment efficiency of the sludge.
The preparation method of tanninic acid complex iron is adopted. By mixing soluble iron salts with tanninic acid aqueous solution, a mixed solution of tanninic acid complex iron is formed, and the pH value is adjusted by alkaline hydroxide to generate precipitated tanninic acid complex iron particles. Finally, the product is obtained by filtration, cleaning and freeze-drying. This product is used in the ozone oxidation system to promote Fe3+/Fe2+ cycle conversion, improve the OH yield, and combine with proteins in the sludge through hydrogen bonding and hydrophobic action to improve the sludge dehydration performance.
The sludge dehydration performance is significantly improved, the moisture content of mud cake is reduced, and the deep dehydration is achieved. The moisture content of mud cake is reduced to 40%-55%, improving the sludge treatment and disposal efficiency.
Smart Images

Figure CN119899229A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a sludge dehydration technology, in particular to a preparation and use method of tannic acid complex iron for enhancing the dehydration performance of ozonated sludge, and belongs to the technical field of environmental engineering. Background Art
[0002] With the accelerated development of my country's social economy and urbanization, the sludge generated by urban sewage treatment plants has also increased sharply. However, due to the high organic matter content, fine particles, and strong hydrophilicity of sludge, its dewatering performance is very poor. After conditioning with conventional aluminum salt or iron salt coagulants, the moisture content of the mud cake obtained by filter pressing is still as high as 75%-85%. Protein is the main biological organic component in sludge, and its content can be as high as 30%-60% of the dry weight of sludge. There are usually a large number of non-covalent interactions such as ionic bonds, van der Waals forces, hydrogen bonds, and hydrophobic interactions between protein molecules, which give it a complex spatial configuration. Therefore, protein is considered to be the main biological macromolecule that affects the dewatering performance of sludge. Its high water retention performance seriously restricts the flow of bound water in sludge. For this reason, it is particularly important to develop a method for efficiently degrading highly hydrophilic proteins in sludge to improve the efficiency of sludge treatment and disposal.
[0003] Using free radicals generated by advanced oxidation technology to degrade proteins in sludge is an effective means to improve the dewatering performance of sludge. Ozone advanced oxidation process has been widely used in wastewater treatment as a green, environmentally friendly, cost-effective and easy-to-operate treatment method. Ozone can directly react with organic matter to undergo electrophilic substitution and dipole addition reactions, but the direct reaction rate is slow and selective, resulting in low pollutant degradation efficiency. Free radical indirect oxidation reactions mainly produce hydroxyl radicals ( · OH) rapidly degrades pollutants non-selectively. Free Fe 2+ Can effectively catalyze the decomposition of ozone · OH, while transforming itself into Fe 3+ , however, Fe 2+ / Fe 3+ The limited circulation results in the inability of the added iron ions to continuously activate ozone to generate free radicals. Furthermore, the non-selective oxidation characteristics of free radicals result in the inability to enhance the decomposition effect of target pollutants, which, to a certain extent, wastes reagents and time. Summary of the invention
[0004] One of the purposes of the present invention is to provide a method for preparing tannic acid complexed iron with enhanced ozonation sludge dewatering performance.
[0005] The second object of the present invention is to provide a method for using the tannic acid complexed iron obtained by the above preparation method.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] In a first aspect, the present invention provides a method for preparing tannic acid complexed iron for enhancing the dewatering performance of ozonated sludge, comprising the following steps:
[0008] (a) mixing a soluble iron salt and a tannic acid aqueous solution to form a tannic acid-complexed iron mixed solution; wherein the molar percentage of the tannic acid to the iron ion is (0.1-10):100;
[0009] (b) adjusting the pH value of the mixed solution in step (a) to 2 to 10 with an alkaline hydroxide aqueous solution to generate precipitated tannic acid-complexed iron particles;
[0010] (c) filtering and washing the precipitate, freeze-drying it, and storing it for later use.
[0011] Preferably, in step (a), the soluble iron salt is one or more of ferric sulfate, ferrous sulfate, ferric nitrate, ferrous nitrate, ferric chloride, ferrous chloride, ferrous acetate, and ferrous acetate; and the molar percentage of tannic acid to iron ions is (0.2-0.8):100.
[0012] Preferably, the alkaline hydroxide in step (b) is sodium hydroxide or potassium hydroxide; and the pH value is preferably 3-7.
[0013] Preferably, the freeze-drying temperature in step (c) is -80 to -50°C and the time is 24 to 90 hours;
[0014] More preferably, the freeze-drying temperature in step (c) is -80 to -65°C and the time is 48 to 72 hours.
[0015] In a second aspect, the present invention provides a method for using the tannic acid complexed iron prepared by the above preparation method, comprising the following steps:
[0016] (1) introducing ozone into organic sludge for pretreatment;
[0017] (2) adding the tannic acid-complexed iron to the ozonated sludge of step (1) and mixing thoroughly;
[0018] (3) ozone is introduced into the mixed solution of the sludge and tannic acid-complexed iron in step (2) for treatment.
[0019] Preferably, in step (1), before adding ozone, the pH value of the sludge is 3.0 to 11.0, more preferably 7.0 to 9.0.
[0020] Preferably, in step (1), the ozone dosage is 20 to 100 mg / gTS, more preferably 40 to 80 mg / gTS.
[0021] Preferably, in step (2), the dosage of the tannic acid complexed iron is 20 to 120 mg / gTS, more preferably 50 to 80 mg / gTS.
[0022] Preferably, in step (3), the amount of ozone added is 10 to 60 mg / gTS, more preferably 20 to 40 mg / gTS.
[0023] The technical principles of the present invention are as follows:
[0024] Tannic acid is a secondary metabolite of plants, which is distributed in the roots, stems, leaves and peels of plants in large quantities. It is naturally green and non-toxic. The ortho-phenolic hydroxyl group in the molecular structure of tannic acid can complex with oxygen anions to form Fe 3+ Form a five-membered ring chelate and further convert Fe 3+ Reduction to Fe 2+ , to achieve Fe 3+ / Fe 2+ Therefore, compared with the single soluble iron salt, the tannic acid complexed iron additive promotes the Fe 2+ Regeneration, strengthening the production of ozone decomposition · OH, greatly improving the oxidation performance of the ozone system; tannic acid complexed iron can bind to a large amount of extracellular proteins released from sludge cells after ozone pretreatment through hydrogen bonds and hydrophobic interactions, thereby shortening the Fe release between proteins and tannic acid complexed iron 2+ Catalytic ozone generation · The action distance of OH is shortened, so the targeted degradation effect of the system on the extracellular protein of sludge is improved; in addition, tannic acid complexed iron itself can be used as an organic-inorganic composite flocculant, which can agglomerate and settle organic fragments, reduce the content of extracellular polymers, increase the particle size of sludge particles, and improve the hydrophobicity of sludge, thereby improving the sludge dewatering performance.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The present invention utilizes tannic acid complexed iron generated by the reaction of tannic acid, a secondary metabolite of natural plants, and iron ions as an additive to the ozone oxidation system, thereby promoting the oxidation of Fe 3+ / Fe 2+ Circular transformation improves · The OH yield rate improves the targeted degradation effect of the ozone oxidation system on the extracellular protein of the sludge, and can increase the degradation effect of the system on the sludge protein by 25%-35%.
[0027] (2) Tannic acid-complexed iron is green, environmentally friendly, non-toxic, and also acts as a flocculant. It can effectively aggregate and settle the organic fragments produced after ozone oxidation sludge, improve the sludge dewatering performance, and achieve deep dehydration (mud cake moisture content <60%). The moisture content of the mud cake after filtration is reduced to 40%-55%, which is beneficial to the subsequent disposal of the sludge. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a process flow chart of improving the dewatering performance of sludge in ozone oxidation system by tannic acid complexed iron;
[0029] Figure 2 This is the microscopic morphology of tannic acid complexed iron under 10000 times scanning electron microscope;
[0030] Figure 3 This is the microscopic morphology of organic sludge under a 10,000x scanning electron microscope;
[0031] Figure 4 This is the microscopic morphology of the sludge after the treatment of tannic acid complexed iron under a 10,000x scanning electron microscope;
[0032] Figure 5 This is the microscopic morphology of the sludge after treatment with tannic acid complexed iron combined with ozone oxidation system under a 10,000x scanning electron microscope. DETAILED DESCRIPTION
[0033] In the first aspect, the present invention provides a method for preparing tannic acid complexed iron with enhanced ozonation sludge dewatering performance, the route is as follows: Figure 1 As shown, the following steps are included:
[0034] (a) mixing a soluble iron salt and a tannic acid aqueous solution to form a tannic acid-complexed iron mixed solution; wherein the molar percentage of the tannic acid to the iron ion is (0.1-10):100;
[0035] (b) adjusting the pH value of the mixed solution in step (a) to 2 to 10 with an alkaline hydroxide aqueous solution to generate precipitated tannic acid-complexed iron particles;
[0036] (c) filtering and washing the precipitate, freeze-drying it, and storing it for later use.
[0037] In some embodiments, in step (a), the soluble iron salt is one or more of ferric sulfate, ferrous sulfate, ferric nitrate, ferrous nitrate, ferric chloride, ferrous chloride, ferrous acetate, and ferrous acetate.
[0038] In some embodiments, in step (a), the molar percentage of tannic acid to iron ions is (0.2-0.8):100 (non-limiting examples include: 0.2:100, 0.3:100, 0.4:100, 0.5:100, 0.6:100, 0.7:100, 0.8:100, etc.).
[0039] In some embodiments, the alkaline hydroxide in step (b) is sodium hydroxide or potassium hydroxide.
[0040] In some embodiments, the pH value in step (b) is 3-7 (non-limiting examples include: 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, etc.).
[0041] In some embodiments, the freeze-drying temperature in step (c) is -80 to -50°C (non-limiting examples include: -80°C, -75°C, -70°C, -65°C, -60°C, -55°C, -50°C, etc.), preferably -80 to -65°C (non-limiting examples include: -80°C, -75°C, -70°C, -65°C, etc.); the time is 24 to 90h (non-limiting examples include: 24h, 36h, 48h, 60h, 72h, 90h, etc.), preferably 48 to 72h (non-limiting examples include: 48h, 60h, 72h, etc.).
[0042] In a second aspect, the present invention also provides a method for using tannic acid complexed iron, the route is as follows: Figure 1 As shown, the following steps are included:
[0043] (1) introducing ozone into organic sludge for pretreatment;
[0044] (2) adding the tannic acid-complexed iron to the ozonated sludge of step (1) and mixing thoroughly;
[0045] (3) ozone is introduced into the mixed solution of the sludge and tannic acid-complexed iron in step (2) for treatment.
[0046] In some embodiments, in step (1), before adding ozone, the pH value of the sludge is 3.0-11.0 (non-limiting examples: 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11.0, etc.), preferably 7.0-9.0 (non-limiting examples: 7.0, 8.0, 9.0, etc.).
[0047] In some embodiments, in step (1), the ozone dosage is 20-100 mg / gTS (non-limiting examples include: 20 mg / gTS, 30 mg / gTS, 40 mg / gTS, 50 mg / gTS, 60 mg / gTS, 70 mg / gTS, 80 mg / gTS, 90 mg / gTS, 100 mg / gTS, etc.), more preferably 40-80 mg / gTS (non-limiting examples include: 40 mg / gTS, 50 mg / gTS, 60 mg / gTS, 70 mg / gTS, 80 mg / gTS, etc.).
[0048] In some embodiments, in step (2), the dosage of the tannic acid complexed iron is 20-120 mg / gTS (non-limiting examples include: 20 mg / gTS, 30 mg / gTS, 40 mg / gTS, 50 mg / gTS, 60 mg / gTS, 70 mg / gTS, 80 mg / gTS, 90 mg / gTS, 100 mg / gTS, 110 mg / gTS, 120 mg / gTS, etc.), more preferably 50-80 mg / gTS (non-limiting examples include: 50 mg / gTS, 60 mg / gTS, 70 mg / gTS, 80 mg / gTS, etc.).
[0049] In some embodiments, in step (3), the ozone dosage is 10-60 mg / gTS (non-limiting examples include: 10 mg / gTS, 20 mg / gTS, 30 mg / gTS, 40 mg / gTS, 50 mg / gTS, 60 mg / gTS, etc.), more preferably 20-40 mg / gTS (non-limiting examples include: 20 mg / gTS, 25 mg / gTS, 30 mg / gTS, 40 mg / gTS, etc.).
[0050] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several changes and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0051] Example 1
[0052] The residual sludge from a sewage treatment plant in Shanghai had a moisture content of 98%. After being filtered at 1.5 MPa for 20 minutes, the moisture content of the mud cake obtained was 78%.
[0053] According to the molar ratio of tannic acid to iron ion of 0.4:100, 0.05 mol / L tannic acid solution and 1 mol / L iron salt solution were mixed, and the pH was adjusted to 6.0 with potassium hydroxide solution. The precipitated tannic acid complex iron was filtered, washed with deionized water for 3 times, and freeze-dried at -80°C for 72 hours. The obtained tannic acid complex iron was placed in a desiccator for later use.
[0054] Ozone was introduced into the sludge reactor to pre-treat the organic sludge (pH=7), and the ozone dosage was 50mg / gTS. Then, tannic acid complexed iron and the ozonation pre-treated sludge were uniformly mixed at a dosage of 35mg / gTS, and then 25mg / gTS ozone was added to the mixed sludge for treatment. The treated sludge was filtered at 1.5MPa using a filter press for 20min, and the obtained mud cake had a moisture content of 52%. However, the dehydration performance of the sludge treated with only 75mg / gTS ozone deteriorated. After dehydration by filter press with the same parameters, the moisture content of the mud cake was as high as 93%.
[0055] Figure 2 This is a microscopic morphology of tannic acid complexed iron under a 10,000x scanning electron microscope; it can be seen that the surface of the prepared tannic acid complexed iron is in a uniform granular accumulation state.
[0056] Figure 3 This is the microscopic morphology of organic sludge under a 10,000x scanning electron microscope. It can be seen that the sludge flocs are arranged in disorder, the surface structure is loose and rough, and thus the sludge dewatering performance is poor.
[0057] Figure 4 This is the microscopic morphology of the sludge after treatment with tannic acid complexed iron under a 10,000x scanning electron microscope, which shows that with the addition of tannic acid complexed iron, the sludge flocs have undergone more obvious changes, and the sludge flocs treated with tannic acid iron have obvious aggregation phenomena.
[0058] Figure 5 This is the microscopic morphology of the sludge after treatment with tannic acid complex iron combined with ozone oxidation system under a 10,000x scanning electron microscope. It can be seen that after treatment with tannic acid complex iron combined with ozone oxidation system, the surface of the sludge flocs is flat and smooth, the arrangement is orderly, there is obvious aggregation phenomenon, and the dewatering performance of the sludge is significantly improved.
[0059] Example 2
[0060] The residual sludge from a sewage treatment plant in Hangzhou had a moisture content of 99%. After being filtered at 1.0 MPa for 25 minutes, the moisture content of the mud cake obtained was 81%.
[0061] According to the molar ratio of tannic acid to iron ion of 0.3:100, 0.05 mol / L tannic acid solution and 2 mol / L iron salt solution were mixed, and the pH was adjusted to 5.5 with potassium hydroxide solution. The precipitated tannic acid complex iron was filtered, washed with deionized water for 3 times, and freeze-dried at -70°C for 60 hours. The obtained tannic acid complex iron was placed in a desiccator for later use.
[0062] Ozone was introduced into the sludge reactor to pre-treat the organic sludge (pH=7), and the ozone dosage was 65mg / gTS. Then, tannic acid complexed iron and the sludge pre-treated by ozonation were uniformly mixed at a dosage of 45mg / gTS, and then 20mg / gTS ozone was added to the mixed sludge for treatment. The treated sludge was filtered at 1.0MPa using a filter press for 25min, and the moisture content of the obtained mud cake was 48%. The dehydration performance of the sludge treated with only 85mg / gTS ozone deteriorated. After dehydration by filter press with the same parameters, the moisture content of the mud cake was as high as 95%.
[0063] Example 3
[0064] The residual sludge from a sewage treatment plant in Suzhou City had a moisture content of 97%. After being filtered at 1.5 MPa for 25 minutes, the moisture content of the mud cake obtained was 79%.
[0065] According to the molar ratio of tannic acid to iron ion of 0.6:100, 0.1 mol / L tannic acid solution and 2 mol / L iron salt solution were mixed, and the pH was adjusted to 6.5 with potassium hydroxide solution. The precipitated tannic acid complex iron was filtered, washed with deionized water for 3 times, and freeze-dried at -75°C for 60 hours. The obtained tannic acid complex iron was placed in a desiccator for later use.
[0066] Ozone was introduced into the sludge reactor to pre-treat the organic sludge (pH=7), and the ozone dosage was 50mg / gTS. Then, tannic acid complexed iron and the ozonation pre-treated sludge were uniformly mixed at a dosage of 40mg / gTS, and then 15mg / gTS ozone was added to the mixed sludge for treatment. The treated sludge was filtered at 1.5MPa using a filter press for 25min, and the obtained mud cake had a moisture content of 45%. However, the dehydration performance of the sludge treated with only 65mg / gTS ozone deteriorated. After dehydration by filter press with the same parameters, the moisture content of the mud cake was as high as 88%.
[0067] Example 4
[0068] The residual sludge from a sewage treatment plant in Changzhou City had a moisture content of 99%. After being filtered at 1.5 MPa for 20 minutes, the moisture content of the mud cake obtained was 80%.
[0069] According to the molar ratio of tannic acid to iron ion of 0.5:100, 0.05 mol / L tannic acid solution and 2 mol / L iron salt solution were mixed, and the pH was adjusted to 6.0 with potassium hydroxide solution. The precipitated tannic acid complex iron was filtered, washed with deionized water for 3 times, and freeze-dried at -75°C for 60 hours. The obtained tannic acid complex iron was placed in a desiccator for later use.
[0070] Ozone was introduced into the sludge reactor to pre-treat the organic sludge (pH=7), and the ozone dosage was 60mg / gTS. Then, tannic acid complexed iron and the ozonation pre-treated sludge were uniformly mixed at a dosage of 40mg / gTS, and then 20mg / gTS ozone was added to the mixed sludge for treatment. The treated sludge was filtered at 1.5MPa using a filter press for 20min, and the obtained mud cake had a moisture content of 47%. However, the dehydration performance of the sludge treated with only 75mg / gTS ozone deteriorated. After dehydration by filter press with the same parameters, the moisture content of the mud cake was as high as 90%.
Claims
1. A method for preparing tannic acid complexed iron for enhancing the dewatering performance of ozonated sludge, characterized in that: The following steps are involved: (a) mixing a soluble iron salt with a tannic acid aqueous solution and stirring to form a tannic acid complexed iron mixed solution; The molar percentage of tannic acid to iron ion is (0.1-10):100; (b) adjusting the pH value of the mixed solution in step (a) to 2 to 10 with an alkaline hydroxide aqueous solution to generate precipitated tannic acid-complexed iron particles; (c) filtering and washing the precipitate, freeze-drying it, and storing it for later use.
2. The method for preparing tannic acid complexed iron for enhancing the dewatering performance of ozonated sludge according to claim 1, characterized in that: In step (a), the soluble iron salt is one or more of ferric sulfate, ferrous sulfate, ferric nitrate, ferrous nitrate, ferric chloride, ferrous chloride, ferrous acetate, and ferrous acetate; the molar percentage of tannic acid to iron ion is (0.2-0.8):
100.
3. The method for preparing tannic acid complexed iron for enhancing the dewatering performance of ozonated sludge according to claim 1, characterized in that: In step (b), the alkaline hydroxide is sodium hydroxide or potassium hydroxide; and the pH value is 3-7.
4. The method for preparing tannic acid complexed iron for enhancing the dewatering performance of ozonated sludge according to claim 1, characterized in that: The freeze-drying temperature in step (c) is -80 to -50°C and the time is 24 to 90 hours.
5. The method for preparing tannic acid complexed iron for enhancing the dewatering performance of ozonated sludge according to claim 4, characterized in that: The freeze-drying temperature in step (c) is -80 to -65°C and the time is 48 to 72 hours.
6. A method for using the tannic acid complexed iron obtained by the preparation method according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) introducing ozone into organic sludge for pretreatment; (2) adding the tannic acid-complexed iron to the ozonated sludge of step (1) and mixing thoroughly; (3) ozone is introduced into the mixed solution of the sludge and tannic acid-complexed iron in step (2) for treatment.
7. The method of use according to claim 6, characterized in that: In step (1), before adding ozone, the pH value of the sludge is 3 to 11, more preferably 7 to 9.
8. The method of use according to claim 6, characterized in that: In step (1), the ozone dosage is 20-100 mg / gTS, more preferably 40-80 mg / gTS.
9. The method of use according to claim 6, characterized in that: In step (2), the dosage of the tannic acid complexed iron is 20 to 120 mg / gTS, more preferably 50 to 80 mg / gTS.
10. The method of use according to claim 6, characterized in that: In step (3), the ozone dosage is 10 to 60 mg / gTS, more preferably 20 to 40 mg / gTS.
Citation Information
Cited By
Protein fiber-iron phytic acid composite flocculant as well as preparation method and application thereof
CN120717589A
Sludge dehydration treatment method
CN121948808A